FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN MELALUI KEPUASAN KERJA PADA TENDIK UNIVERSITAS 17 AGUSTUS 1945 SURABAYA - Sumiati (STIE Mahardhika, 2024)
This research aims to determine and analyze the influence of discipline, teamwork, and quality of work life on employee performance, with job satisfaction as an intervening variable, among educational personnel at the University of 17 August 1945 Surabaya. Data collection was carried out by distributing questionnaires using a Likert scale. The sample consisted of 100 educational staff, selected using the Probability Sampling technique with Simple Random Sampling. The results indicate that discipline has a significant effect on both job satisfaction and employee performance. Similarly, teamwork and quality of work life significantly affect job satisfaction and employee performance. Furthermore, job satisfaction significantly influences employee performance. Discipline and quality of work life positively influence employee performance through job satisfaction as an intervening variable, while teamwork does not have a significant indirect effect on employee performance through job satisfaction.